Amitriptyline Intoxication in Children: Twenty Years' Experience in a Tertiary Care Center in Turkey. Issue 12 (December 2021) - Kamasak, Tülay; Kader, Şebnem; Mutlu, Mehmet; Özkaya, Kagan; Erduran, Erol; Orhan, Fazıl; Dilber, Embiya; Kalyoncu, Mukaddes; Karagüzel, Gülay; Cakır, Murat; Bahat, Elif; Cansu, Ali
Abstract : Background: Amitriptyline ingestion is an important cause of poisoning morbidity and mortality in Turkey and other countries. In contrast to adults, data concerning amitriptyline intoxication in children are limited. The purpose of this study was to investigate amitriptyline intoxication findings in the pediatric population, based on age groups and reported dosages. Methods: The medical records of 192 patients admitted to the Karadeniz Technical University Medical Faculty Farabi Hospital Pediatric Emergency Department, Turkey, due to amitriptyline intoxication in 1997–2017 were examined retrospectively. Patients were divided into 6 groups based on amitriptyline doses and 4 groups based on age. Complete blood count, blood glucose, serum electrolytes, renal and liver function tests, coagulation tests (prothrombin time and partial thromboplastin time), and blood gas analysis were studied in all patients. Electrocardiography was performed on all children, and chest radiography and electroencephalography on those with respiratory or central nervous system symptoms. Results: Amitriptyline intoxication was most frequently observed between the ages of 1 and 4 years. The most common signs and symptoms observed at time of hospital admission were lethargy and drowsiness (45.3%), sinus tachycardia (19.2%), and nausea and vomiting (13%). The most common laboratory finding was hyperglycemia (17.7). Six patients were intubated because of respiratory failure, and mechanical ventilation was initiated in these cases. One patient with amitriptyline overdose had persistent supraventricular tachycardia. Four children died due to amitriptyline intoxication. Conclusions: Tricyclic antidepressant intoxication is a leading cause of mortality and morbidity in children. It is therefore particularly important to identify the clinical and laboratory findings that develop with high-dose consumption.